The Effects of Fusion Structure on the Expression and Bioactivity of Human Brain Natriuretic Peptide (BNP) Albumin Fusion Proteins - Ding, Yuedi; Peng, Ying; Deng, Lili; Wu, Yu; Fu, Qiang; Jin, Jian (Current Pharmaceutical Biotechnology, 2014)
Human brain natriuretic peptide (BNP) is utilized in the treatment of acute decompensated congestive heart failure. However, BNP has limited clinical use owing to its rapid clearance and the need for continuous intravenous infusion. Thus, we generated human serum albumin (HSA)-BNP fusion constructs to produce long-acting fusion proteins in Pichia pastoris. Four fusion proteins, BNP–HSA, (BNP)2–HSA, (BNP)4–HSA, and HSA–(BNP)2, were constructed, with different numbers of BNP molecules and fusion orientations. BNP–HSA was most abundantly expressed in Pichia pastoris and (BNP)4–HSA had the lowest yield, probably because of the high copy number of BNP. Western blot analysis confirmed the immunogenicity of both BNP and HSA for the four fusion proteins. A cGMP activity assay was used to measure the ability of fusion proteins to stimulate intracellular cGMP expression. Results showed that the fusion protein HSA–(BNP)2 activated human natriuretic peptide receptor A (hNPR-A) with potency similar to that of BNP, despite using a 10-fold higher dosage than BNP. The other three fusion proteins (BNP–HSA, (BNP)2–HSA, and (BNP)4–HSA), only slightly increased NPR-A activity. In addition, fusion with HSA successfully prolonged BNP bioactivity, stimulating intracellular cGMP expression over 24 h. In conclusion, HSA–(BNP)2, with two BNP molecules fused at the C-terminus of HSA, has the highest and most prolonged BNP bioactivity in activating human NPR-A.
Keywords: brain natriuretic peptide